Kajian Ekonomi Syariah Dalam Pelaksanaan Asuransi Jaminan Kesehatan Pada Faskes Pertama Layanan BPJS Puskesmas Palasari Subang - Kiki Erika; Rina Nurhayati; Moch. Cahyo Sucipto (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
This research was conducted at the Palasari Ciater Health Center in Subang Regency. Puskesmas is one of the first-level health institutions in collaboration with BPJS. BPJS is a legal entity formed to organize social security programs, BPJS consists of BPJS Health and BPJS Employment. BPJS Health runs a health insurance program, while BPJS Employment operates a work accident insurance program, old age insurance, pension insurance and death insurance. This study aims to find out how the implementation of BPJS Health in the first Health Center in Palasari Ciater Subang Health Center and how the view of the Ekonmi Syariah related to the implementation of the first level BPJS Health in the first Health Center in Palasari Ciater Subang Health Center. This type of research is qualitative using descriptive analysis method. Data sources used include primary and secondary data. From the results of the discussion the researchers found that in its implementation all Indonesian citizens were required to become members of the Health BPJS. In its implementation at the Palasari Puskesmas openly serves all the important BPJS Health participants, they come to the Puskesmas carrying a card and then click on the ticket and they are active members. The implementation of health insurance (BPJS Kesehatan) at the Palasari Health Center in terms of service has been carried out in accordance with the law, and in accordance with the Sharia Economy.